Pemikiran Hans-Georg Gadamer Dari Sudut Pandang Doktrin Injili Di Indonesia - Tejalaksana, Sandy (Sekolah Tinggi Teologi Injili Indonesia Palu, 2026)
This study examines the hermeneutical thought of Hans-Georg Gadamer, particularly his concepts of prejudice, dialogue, historicity, tradition, and the fusion of horizons, as well as how these concepts interact with the Evangelical doctrine in Indonesia, which emphasizes the absolute authority of the Bible. Through a qualitative approach based on literature review and comparative analysis, the study demonstrates that Gadamerian hermeneutics can enrich the understanding of Evangelical theology within Indonesia’s multicultural context, especially in contextualized evangelism and interfaith dialogue. However, Gadamer’s approach also generates tension with Evangelical principles, particularly regarding the authority of revelation, the relativism of meaning, and the risk of syncretism. This research offers a critical and reflective synthesis of the two approaches and proposes the development of a more dialogical, contextual, and relevant Evangelical hermeneutics capable of addressing Indonesia’s cultural and religious plurality.